2015
DOI: 10.4238/2015.july.14.12
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of primer affinity improves high-resolution melting accuracy for imprinted genes

Abstract: ABSTRACT. High-resolution melting (HRM) is considered an inexpensive, rapid, and attractive methodology for methylation analysis. In the application of the polymerase chain reaction (PCR) to methylation analysis, amplification efficiencies are biased towards unmethylated, rather than methylated, templates: a phenomenon known as PCR bias. To overcome PCR bias, primers that include CpG site(s) and are fully complementary to the methylated sequence have been proposed. However, genes mapped within imprinted region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…However, several important points about the HRM method have been proposed; improved efficiency is probably due to the short length of primers, which enabled better amplification in PCR. Furthermore, the concentration of primers has an important role in increasing the sensitivity and specificity of HRM assay (Rubatino et al ; Słomka et al ). The sensitivity of these primers performed that with this technology, template DNA can be amplified exponentially starting from very low concentrations in the initial sample.…”
Section: Resultsmentioning
confidence: 99%
“…However, several important points about the HRM method have been proposed; improved efficiency is probably due to the short length of primers, which enabled better amplification in PCR. Furthermore, the concentration of primers has an important role in increasing the sensitivity and specificity of HRM assay (Rubatino et al ; Słomka et al ). The sensitivity of these primers performed that with this technology, template DNA can be amplified exponentially starting from very low concentrations in the initial sample.…”
Section: Resultsmentioning
confidence: 99%
“…Although aforementioned results were consistent with PWS, genetic testing was resumed at 12 years of age due to their atypical phenotype. Methylation‐sensitive high resolution melting (MS‐HRM) (Rubatino et al, ), performed on peripheral blood DNA, confirmed methylation of the SNURF‐SNRPN promoter in both twins (Supplementary Figure S2). Taking into consideration the presence of some symptoms of Angelman Syndrome (AS, MIM #105830) such as apparent ID, microcephaly, lack of speech, autistic features, and epilepsy, it was hypothesized that the UBE3A gene on the non‐deleted chromosome was potentially silenced by a mutation.…”
Section: Clinical Reportmentioning
confidence: 65%
“…Primers sequences for the amplification of the SNRPN (NG_012958.1) gene were designed based on the methodologies of Rubatino et al, 2015. In summary, the designed forward primer established a perfect match with the unmethylated template, while the reverse primer exhibited one mismatch with the methylated template.…”
Section: Primer Design and Sequencesmentioning
confidence: 99%